The Role of High-Content Complex Dietary Fiber in Medical Nutrition Therapy for Gestational Diabetes Mellitus - Wang, Hong-Kun; Cheng, De-Cui; Yang, Yue-Min; Wang, Xia-Hong; Chen, Yan; Zhang, Lin; Xiu, Lian; Xu, Xian-Ming (Frontiers in Pharmacology, 2021)
Objectives: A controlled open clinical study was conducted to evaluate the role of Ricnoat, a high-content complex dietary fiber powder produced by Zhuhai Aimed Biotechnology Co. Ltd., in medical nutrition therapy (MNT) to treat gestational diabetes mellitus (GDM). The study aimed to investigate glycemic control, lipid control, weight control, and pregnancy outcomes (neonatal weight) in patients with GDM, as well as evaluate the clinical safety of Ricnoat. Methods: A total of 120 patients with GDM who were admitted to three hospitals in Shanghai between January 2019 and January 2020 were enrolled. Ricnoat was used for intervention for patients in the experimental group. Using a χ2 test and t-test, respectively, comparisons were conducted between the measurement data and countable data of the demographics and baseline disease characteristics of the experimental group and control group. Results: Fasting blood glucose, two-hour postprandial blood glucose, glycated hemoglobin, total cholesterol, triglycerides, low-density lipoprotein, maternal gestational weight gain, neonatal weight, serum creatinine, glutamate transaminase, and aspartate aminotransferase were lower in the experimental group than in the control group, whereas high-density lipoprotein was higher in the experimental group than in the control group. Ricnoat intervention resulted in satiety higher than the expected 80% and more common occurrence of type 4 (smooth and soft, like salami or a snake) and type 5 (a soft mass with clear edges) stools. Conclusions: Ricnoat intervention had a significant effect on glycemic control, lipid control, weight control, and pregnancy outcomes (neonatal weight) in patients with GDM by enhancing maternal satiety and improving the stool features of pregnant women. It was also found to be safe for application during pregnancy.